African Journal of Urology - Khalaf, Ismail; Waltregny, David; ElSheemy, Mohammed; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
African Journal of Urology (AFJU) plays an important and recognised role in contributing to the understanding of urological diseases. The journal is an open access peer reviewed journal publishing quality research that covers urological oncology related issues, endourology, robotic and laparoscopic surgery, pediatric urology, functional urology, renal transplantation, urolithiasis, genitourinary medicine, andrology, uro-pharmacology, uro-radiology, prevention, as well as female and reconstructive urology. AFJU aims to bridge the gap between African urologists and other international experts by providing a platform for the dissemination of quality research. The journal welcomes submissions of original research, review, short communications and case reports. .
Keywords: Surgery; Urology; Imaging systems in biology; Surgery; Urology; Biological Imaging